(untitled) (Research, Society and Development, 2021)
The aim of this article was to carry out a study of nutrients and herbal medicines that can be used as an adjunct to help strengthen the immune system. Therefore, this is an explanatory descriptive bibliographic analysis that includes a bibliographic review and contains a time frame from 2013 to 2021. The information obtained was taken from databases of scientific documents, selecting documents described in English and Portuguese, which reporting on reactions with SARS-CoV-2 the interaction of healthy eating in daily life is indeed very important in addition to other care methods. Medicinal plants can comfort and fight various infectious diseases. The organism, when you have an infection, is quite vulnerable since microorganisms harm causing cell deficiencies, even if the organism has cells that destroy them, however it needs nutrients that make the immune system preferentially fit, preserving the balance for functioning From protection the immune system acts to protect the body daily from attacks against infections, when viruses such as SARS-CoV-2 dominate the body, the cells take action to fight the virus and possibly obtain a cure or improvement for the individual. Therefore, based on the reviewed literature, it was concluded that adjuvants such as healthy eating and herbal medicines are willing to contribute to nutrient replacement capable of strengthening the individual’s immunity.